2019
DOI: 10.1177/2158244018823079
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Ban Versus Border Rejections: A Case of Oman’s Fish Exports to the EU

Abstract: The decline of Oman's fish exports to the European Union (EU) since mid-2000s has caused legitimate concerns among policy makers and exporters. However, the potential reasons for the decline have not been fully elucidated. To ascertain the underlying causes of such decline, this article empirically examines the relative significance of potential economic and policyrelated factors such as border rejections influenced by health and safety measures, supply and demand capacities, domestic ban, domestic structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…Therefore, the results provide support to Research Hypothesis 1 only for the EU market. This is consistent with the findings by Bose et al (2019) who noted the domestic export ban rather than the border rejections by the EU countries has acted as a significant barrier to fish exports to the EU. A recent study conducted by Al-Busaidi et al (2017) stated that the share of Oman's end products going to lucrative markets such as the EU, the United States, and Japan declined due to the exports ban on specific species.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the results provide support to Research Hypothesis 1 only for the EU market. This is consistent with the findings by Bose et al (2019) who noted the domestic export ban rather than the border rejections by the EU countries has acted as a significant barrier to fish exports to the EU. A recent study conducted by Al-Busaidi et al (2017) stated that the share of Oman's end products going to lucrative markets such as the EU, the United States, and Japan declined due to the exports ban on specific species.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of New Zealand lobster export to Japan, Bose and Galvan (2005) noted that 39% of the gap between the actual and desired level was covered in each period. For the EU market case using yearly data, Bose et al (2019) found that 1.92 1.94 Heteroscedasticity B-P-G: χ 2 = 1.58 (df = 10) (p = .14) B-P-G: χ 2 = 7.43 (df = 9) (p = .59) ARCH: χ 2 = 1.00 (df = 1) (p = .32) ARCH: χ 2 = 0.64 (df = 1) (p = .42) FSB (2001FSB ( -2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory was enhanced by adding a multilateral resistant variable that reflects the average distance of a country from all other countries. In the more recent literature, the gravity model was applied to a variety of trade issues, including trade integration patterns (Rasoulinezhad & Jabalameli, 2018;Rasoulinezhad et al, 2020), energy exports (Rasoulinezhad & Jabalameli, 2019), agro-food exports (Crescimanno et al, 2013), and fishery exports (Bose et al, 2019). Following the literature, the model to be estimated in this study takes the following empirical form:…”
Section: The Modelmentioning
confidence: 99%